Improving Arabic Academic Writing Skills Through Contextual Teaching And Learning Approach - Muhammad Kamal bin Abdul Hakim; Yumna Rasyid; Zainal Rafli (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The aim of this study is to examine the effect of contextual teaching and learning approach to the Arabic academic writing skills students of Education Arabic Department Faculty of Language and Arts State University of Jakarta. The research was conducted during the second semester in the 2015/2016 academic year starting from February up June in 2016. The study design used Elliot’s procedure, which comprised seven phases, namely: (a) identifying the initial ideas, (b) finding and analyzing the facts, (c) general planning, (d) Implementing, (e) observing, (f) evaluating, and (g) revising. The data were taken by observation, interview, and test. The results of the study found that the mean of the pre-test was 65,30, the average score results of the test at the first cycle were 73,25, the average score of the test at the second cycle was 77,40, and the average score of the test at third cycle was 84.1. During the learning process, students have shown the changing of learning behaviour and meet the criteria either by 80%. The quality of students' academic writing has also shown significant. It concluded that the contextual teaching and learning approach could improve the student’s skill in Arabic academic writing.